Clinical features of tic-related obsessive-compulsive disorder: results from a large multicenter study - de Alvarenga, Pedro Gomes; de Mathis, Maria Alice; Dominguez Alves, Anna Claudia; do Rosario, Maria Conceicao; Fossaluza, Victor; Hounie, Ana Gabriela; Miguel, Euripedes Constantino; Torres, Albina Rodrigues [UNESP] (Cambridge University Press, 2012)
Objective. To evaluate the clinical features of obsessive-compulsive disorder (OCD) patients with comorbid tic disorders (TD) in a large, multicenter, clinical sample.Method. A cross-sectional study was conducted that included 813 consecutive OCD outpatients from the Brazilian OCD Research Consortium and used several instruments of assessment, including the Yale-Brown Obsessive-Compulsive Scale, the Dimensional Yale-Brown Obsessive-Compulsive Scale, the Yale Global Tic Severity Scale (YGTSS), the USP Sensory Phenomena Scale, and the Structured Clinical Interview for DSM-IV Axis I Disorders.Results. The sample mean current age was 34.9 years old (SE 0.54), and the mean age at obsessive-compulsive symptoms (OCS) onset was 12.8 years old (SE 0.27). Sensory phenomena were reported by 585 individuals (72% of the sample). The general lifetime prevalence of TD was 29.0% (n=236), with 8.9% (n=72) presenting Tourette syndrome, 17.3% (n=5141) chronic motor tic disorder, and 2.8% (n=523) chronic vocal tic disorder. The mean tic severity score, according to the YGTSS, was 27.2 (SE 1.4) in the OCD1TD group. Compared to OCD patients without comorbid TD, those with TD (OCD1TD group, n=236) were more likely to be males (49.2% vs. 38.5%, p<005) and to present sensory phenomena and comorbidity with anxiety disorders in general: separation anxiety disorder, social phobia, specific phobia, generalized anxiety disorder, post-traumatic stress disorder, attention-deficit hyperactivity disorder, impulse control disorders in general, and skin picking. Also, the "aggressive," "sexual/religious," and "hoarding" symptom dimensions were more severe in the OCD+TD group.Conclusion. Tic-related OCD may constitute a particular subgroup of the disorder with specific phenotypical characteristics, but its neurobiological underpinnings remain to be fully disentangled.
Keywords: Comorbidity; obsessive-compulsive disorder; tic disorder; Tourette syndrome